2015
DOI: 10.1016/j.jpeds.2014.12.041
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Loss by Week of Gestation and Birth Weight in Very Preterm Neonates

Abstract: Gestational age and birth weight quantify the risk of NHL. This information can be used at the individual level for parent counseling and at the population level for medical decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
3
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 18 publications
1
25
3
8
Order By: Relevance
“…Though prematurity is a common risk factor in our study group, no significant association was found in statistical analysis between prematurity and hearing impairment. This is in contrast to the study by Paula van et al which showed an increase in incidence of hearing impairment with decreasing gestational age(1.2% -7.5% from 31 to 24 weeks) (10) . In our study the incidence of hearing loss in preterm babies is 4.79%.…”
Section: Discussioncontrasting
confidence: 97%
“…Though prematurity is a common risk factor in our study group, no significant association was found in statistical analysis between prematurity and hearing impairment. This is in contrast to the study by Paula van et al which showed an increase in incidence of hearing impairment with decreasing gestational age(1.2% -7.5% from 31 to 24 weeks) (10) . In our study the incidence of hearing loss in preterm babies is 4.79%.…”
Section: Discussioncontrasting
confidence: 97%
“…14 Admission to a neonatal intensive care unit is a relevant risk factor; with the prevalence of hearing loss increasing as gestational age and birth weight decrease (1.2–7.5% in premature babies born at 24–31 weeks and 1.4%–4.8% in babies weighing 750–1500 g). 15 Necessary medical interventions (such as assisted ventilation, venous access and aminoglycoside use) while in the neonatal intensive care unit increase the likelihood of hearing loss. Duration of hospitalization of ≥12 days and a history of treatment by high-frequency ventilation have also been identified as independent risk factors for hearing loss in this population.…”
Section: Epidemiologymentioning
confidence: 99%
“…Preterm infants experience higher rates of respiratory distress syndrome, bronchopulmonary dysplasia, necrotising enterocolitis, kernicterus, hypoglycaemia, periventricular leucomalacia, seizures, intraventricular haemorrhage, cerebral palsy, infections, feeding difficulties, hypoxic ischaemic encephalopathy, retinopathy of prematurity, as well as visual and hearing loss. [5][6][7][8][9][10][11][12][13][14][15][16] Preterm birth and its sequelae can have significant negative psychosocial and financial impacts on families of preterm newborns. [17][18][19][20] While the risks of mortality and morbidity affecting preterm newborns are considerably more frequent at lower gestational ages, 11 late preterm infants (sometimes called 'near-term') still experience significantly higher risks compared with babies born at term.…”
Section: Bmj Global Healthmentioning
confidence: 99%